Experimental regulatory environments: sandbox in the Brazilian financial system - Missagia, Caio Rezende (2023)
The paper discusses the first proposals for the adoption of the regulatory sandbox (herein referred to as experimental regulatory environment) in Brazil. This institute was pioneered by Complementary Law 182/2021 (Legal Framework for Startups), and has been developed in the regulation of the national financial system through the initiatives of the Superintendence of Private Insurance (Susep), the Securities and Exchange Commission (CVM), and the Central Bank of Brazil (BCB). Anchored in a socio-legal literature, the paper mapped these initiatives and analyzed them in light of the hypothesis that experimental regulatory environments are alternatives to two basic models of regulatory law in general, and of financial regulation in particular: the model of centralized and detailed regulation, typical of the welfare state, and the model of deregulation characteristic of neoliberalism. In a trans-nationalized economy, the regulatory sandbox allows national regulators to develop experimental forms of law that lower barriers to entry for new service providers – in this case, it increases the potential for innovative financial services (such as fintechs), which can counter the high banking concentration in the Brazilian market.